2021
DOI: 10.1039/d1ta05148b
|View full text |Cite
|
Sign up to set email alerts
|

Highly stretchable, bionic self-healing waterborne polyurethane elastic film enabled by multiple hydrogen bonds for flexible strain sensors

Abstract: Flexible elastomer material with high stretchability and self-healing performance is the preferred substrates for preparing multi-function flexible sensors and bionic electronic skin. However, it is still a great challenge to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…After being incorporated into the polymer network, this unique structure of castor oil led to the formation of dangling chains and network defects. These phenomena were also reported previously by other research groups. The glass transition temperature ( T g ) values of the polyurethane films were obtained from the temperature corresponding to the peak of the tan δ curves. When the molar ratios between amine groups of RN and the OH groups of castor oil increased from 0:10 to 5:5, the T g values of samples exhibited an increase from −40.8 to 37.6 °C. The similar trend of the T g was obtained from DSC as a function of temperature (Figure c).…”
Section: Resultssupporting
confidence: 79%
“…After being incorporated into the polymer network, this unique structure of castor oil led to the formation of dangling chains and network defects. These phenomena were also reported previously by other research groups. The glass transition temperature ( T g ) values of the polyurethane films were obtained from the temperature corresponding to the peak of the tan δ curves. When the molar ratios between amine groups of RN and the OH groups of castor oil increased from 0:10 to 5:5, the T g values of samples exhibited an increase from −40.8 to 37.6 °C. The similar trend of the T g was obtained from DSC as a function of temperature (Figure c).…”
Section: Resultssupporting
confidence: 79%
“…[36] The absorption peak at 1712 cm À1 is assigned to C=O groups of -CONHin the PU chains, indicating the successful syntheses of the PU polymer. [30,37] IU was the physical crosslinking site in the system that increased the tensile strength of the material. The multiple hydrogen bonds in the IU structure and ionic bonds were first dissociated due to energy dissipation, and then the mechanical properties of the material were restored by the recombination of the multiple hydrogen bonds and ionic bonds.…”
Section: Design Strategy and Microstructure Of The Wpu/emim:dca Ionogelsmentioning
confidence: 99%
“…[ 28,29 ] In addition, the multiple hydrogen bonds combined into microdomains can provide strong bonding energy thus enhancing the strength of the material. [ 30,31 ] Song et al [ 32 ] proposed the construction of high‐strength, high‐toughness elastomers from the hydrogen bonding interactions of 2‐ureido‐4[1H]‐pyrimidione (UPy). However, the introduction of UPy usually requires a complicated chemical modification before introducing into the polymer system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the introduction of HTF replaces part of the disul de bond. Although the content of the disul de bond is reduced, the introduction of HTF increases the degree of hydrogen bonding of polyurethane, and Studies have shown that the existence of dynamic hydrogen bonding will promote the healing process of polyurethane [39][40][41]. Figure 5b shows the properties of the FT-IR spectral bands of the vibrations of the C = O group in SFPUHE-HTF.…”
Section: Self-repair Performance and Repair Mechanism Of Sfpuhe-htf A...mentioning
confidence: 99%